MODEL LATIHAN TEKNIK DASAR FUTSAL (AS) BERBASIS PERMAINAN UNTUK ANAK USIA SMP - Arrahman; Firmansyah Dlis; Yasep Setia Karrnawijaya (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2019)
The goal of this development research is to produce a book product model of basic futsal (AS) game-based technique skills training that can provide benefits to trainers to facilitate trainers in implementing training materials. This research uses research and development model of Research and Development from Borg and Gall which consists of ten steps in research. The experimental research design is the twogroup pretest-posttest design. Subjects in this study were junior high school students consisting of 40 students with 28 items of exercise model and 40 students were not treated. Stages in this study are: preliminary research, expert evaluation, product trial consisting of small group try-out and field try group, and test product effectiveness. The model effectiveness test uses basic engineering skill tests by comparing control and experiment groups. The experimental group was performed by pre-test before the treatments and post-test after treatment. While the control group was given pre-test and post-test but not given treatment. . The comparison test of control and experiment group with spss-16 then the control group is passing = 0.218, controlling = 0.684, dribbling = 0.456, shooting = 0.271 or p-value> 0.05 then there is no significant difference in the control group. While in the experimental group is passing = 0.000, controlling = 0.000, dribbling = 0.000, shooting = 0.000 or p-value <0.05 then there is a significant difference in the experimental group before and after treatment. Thus the application of the basic technique-based futsal (AS) skill training model for the age of junior high school needs to be done to improve the students' basic engineering skills. Abstrak Tujuan yang ingin dicapai dari penelitian pengembangan ini adalah untuk menghasilkan produk buku model latihan keterampilan teknik dasar futsal (AS) berbasis permainan yang dapat memberikan manfaat kepada pelatih untuk mempermudah pelatih dalam menerapkan materi latihan. Penelitian ini menggunakan model penelitian dan pengembangan Research and Development dari Borg dan Gall yang terdiri dari sepuluh langkah dalam penelitian. Rancangan penelitian eksperimen berbentuk the two group pretest-posttest design. Subjek dalam penelitian ini merupakan siswa usia SMP yang terdiri dari 40 siswa dengan 28 item model latihan dan 40 siswa tidak diberi perlakuan. Tahapan dalam penelitian ini adalah: penelitian pendahuluan, evaluasi pakar, uji coba produk yang terdiri dari small group try-out dan field try group, serta uji efektivitas produk. Uji efektivitas model menggunakan tes keterampilan teknik dasar dengan membandingkan kelompok kontrol dan eksperimen. Kelompok eksperimen dilakukan dengan memberikan pre-test sebelum treatmen dan post-test setelah treatment.Sedangkan kelompok kontrol diberikan pre-test dan post-tes namun tidak diberikan treatment..Uji perbandingan kelompok kontrol dan eksperimen dengan spss-16 adalahpassing = 0.030, controlling = 0.002, dribbling = 0.000, shooting = 0.024 atau p-value < 0.05 maka terdapat perbedaan yang signifikan pada kelompok kontrol dan kelompok eksperimen sebelum dan setelah pemberian treatment.Dengan demikian penerapan model latihan keterampilan teknik dasarfutsal (AS)berbasis permainan untuk usia SMP perlu dilakukan untuk meningkatkan kemampuan teknik dasar siswa. Kata Kunci: Model, Latihan, Futsal, Teknik Dasar, Permainan